A systematic review of studies on Facebook as a social forum - Zikargae, Mekonnen Hailemariam (IJRDO - Journal of Social Science and Humanities Research, 2018)
The aim of this study is to present a review of Facebook as a social forum. To this effect, articles are reviewed analytically by collecting the existing information based on the key terms or words related to the study of Facebook as a social forum. The result depicts that Facebook gets through the different terrain of the social media landscape. The review also indicates that Facebook is predominantly used to discuss social issues like education and human rights. In addition, it shows that Facebook has strengths, opportunities, weaknesses, and threats. Further, Facebook users have been troubled due to a cybercrime. In the end, the reviewer puts about signposts of current situations towards the use of Facebook and its future implication specifically in the context of African countries.